Methods for Condition Assessment of the High Voltage Circuit Breakers Based on Vibration Fingerprint—A Survey - Kerim Obarcanin; Bakir Lacevic (IEEE Access)
The critical role of high-voltage circuit breakers in the power grid underscores the need for reliable and efficient methods to assess their condition and operational parameters. To support the integration of smart grid concepts and enable condition assessment during circuit breaker exploitation, non-invasive approaches are essential. Among these, methods leveraging vibration fingerprints generated during the opening or closing of circuit breakers have shown significant promise. This paper presents a comprehensive survey of state-of-the-art research in this area, systematically analyzing over 100 influential works from the past two decades. The survey categorizes these methods based on their domain-specific approaches and highlights key challenges related to signal analysis, data acquisition, feature extraction, interpretation, and reasoning. By offering a structured analysis, this survey serves as a valuable resource for researchers and practitioners, providing insights and direction for future advancements in this niche field.